Effects of IFN-γ coding plasmid supplementation in the immune response and protection elicited by Trypanosoma cruzi attenuated parasites - Pérez Brandan, Cecilia María (2017)
Background: Previous studies showed that a naturally attenuated strain from Trypanosoma cruzi triggers an immune response mainly related to a Th2-type profile. Albeit this, a strong protection against virulent challenge was obtained after priming mice with this attenuated strain. However, this protection is not enough to completely clear parasites from the host. In T. cruzi infection, early Interferon-gamma (IFN-γ) is critical to lead type 1 responses able to control intracellular parasites. Therefore we evaluated whether the co-administration of a plasmid encoding murine IFN-γ could modify the immune response induced by infection with attenuated parasites and improve protection against further infections. Methods: C57BL/6J mice were infected intraperitoneally with three doses of live attenuated parasites in combination with plasmid pVXVR-mIFN-γ. Before each infection dose, sera samples were collected for parasite specific antibodies determination and cytokine quantification. To evaluate the recall response to T. cruzi, mice were challenged with virulent parasites 30 days after the last dose and parasite load in peripheral blood and heart was evaluated. Results: As determined by ELISA, significantly increase in T. cruzi specific antibodies response was detected in the group in which pVXVR-mIFN-γ was incorporated, with a higher predominance of IgG2a subtype in comparison to the group of mice only inoculated with attenuated parasites. At our limit of detection, serum levels of IFN-γ were not detected, however a slight decrease in IL-10 concentrations was observed in groups in which pVXVR-mIFN-γ was supplemented. To analyze if the administration of pVXVR-mIFN-γ has any beneficial effect in protection against subsequent infections, all experimental groups were submitted to a lethal challenge with virulent bloodstream trypomastigotes. Similar levels of challenge parasites were detected in peripheral blood and heart of mice primed with attenuated parasites alone or combined with plasmid DNA. Expansion of IgG antibodies was not significant in TCC+ pVXVR-mIFN-γ; however, the overall tendency to sustain a Th2 profile was maintained. Conclusions: Overall, these results suggest that administration of plasmid pVXVR-mIFN-γ could have beneficial effects on host specific antibody production in response to T. cruzi attenuated infection; however, this outcome is not reflected in an improved protection against further virulent infections.